Effect of Deficit Sprinkler Irrigation on the Biophysical Performance of Vegetative Stage of Banana Cavendish Musa AAA cv. Williams - Monge-Freile, Marlon Fernando; Álvarez Sánchez, Ana Ruth; Villamar-Torres, Ronald Oswaldo; Molina Yépez, Katiuska Carolina; Issaka Salia, Ousseini; Jazayeri, Seyed Mehdi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
This research aimed to evaluate the agronomic effect of deficit sprinkler irrigation sin the cultivation of banana Cavendish Musa AAA cv. Williams in Ecuador. Four treatments were carried out with different irrigation levels: T1 (40% of ETc (evapotranspiration of the crop)), T2 (60% of ETc), T3 (80% of ETc), and T4 (100% of ETc), with a design of complete random blocks and three repetitions. The results showed that the crop exhibited better biophysical behavior when irrigated at 100% of ETc throughout the study period, with higher values in total leaves and root weight, while there were no significant differences for plant height, pseudostem diameter, and leaf emission. T1 achieved greater efficiency, managing with less volume to convert the same amount of matter in vegetative development. Finally, the cost of irrigation application during weeks 5 to 16 of the crop's age was higher in treatment T4 (100% of ETc) due to the larger volume of water used in the irrigation system. It is concluded that the use of controlled deficit irrigation helps save large amounts of water, which translates into savings for farmers and better water distribution due to the effects of climate change from the reduction of flow rates.